QUALITY ASSURANCE IN HIGHER EDUCATION: UP-TO-DATE EXPERIENCE (PAPER 2) - V. I. Baidenko; N. A. Selezneva (Высшее образование в России)
The paper presents a panorama of European Quality Assurance Forums (EQAF) and their topical focus. The authors give their opinion that for the purposes of academic communication we need to develop a glossary completely reflecting theoretical, conceptual, methodological and practical wealth in this area. While addressing topics within the whole “perimeter” of all forums held, the paper focuses mainly on the selected materials of the eighth EQAF. The authors consider issues concerning the defining of the concept of “higher education quality” and developing the institutional quality culture. The paper dwells on the barriers to European Standards and Guidelines for Quality Assurance (ESG) implementation. Attention is given to accreditation processes, especially to the balance between “accountability” and “enhancement”. The paper also touches upon the issues of criteria validity and the indicators for higher education quality.